The Associations Between Maternal Mentalization Ability and Cognitive Functions - Rusanen, Hannele (My University, 2020)
A child’s secure attachment to his/her primary caregiver is of great importance for the well-being of the child. Parental mentalization plays an important role in the infantparent attachment security. Research regarding the possible effects that maternal cognitive abilities might have on the maternal mentalizing is still rather sparse, mostly focusing on the executive functions. The aim of the present study was to investigate the relationship between maternal mentalization and cognitive functions. The second aim was to explore whether maternal depression and/or anxiety moderate these associations. The sample (n = 240 mothers) was drawn from the FinnBrain Birth Cohort Study. Maternal mentalization was assessed with the Parental Reflective Functioning Questionnaire (PRFQ-fi). Four composites of cognitive functions were used to measure maternal cognition, three of these (i.e., Executive functions, Processing speed, Verbal learning) were constructed based on CogState Battery tasks, the fourth was the Verbal Comprehension Index (VCI) from the Wechsler Adult Intelligence Scale IV. In assessing maternal mental health, the Edinburgh Postnatal Depression Scale (EPDS) was used for the depressive, and the Symptom Checklist/anxiety subscale (SCL-90) for the anxiety symptoms. The results showed that the PRFQ-fi subscale Understanding the opaque nature of mental states was positively associated with Verbal learning and with Verbal intelligence. Moreover, the PRFQ-fi subscale Appropriateness of reasoning about mental states underlying child's reactions was positively associated with Verbal intelligence. No significant results were found for the PRFQ-fi subscales Interest and curiosity in child's individual mental states or Acknowledging the uncertainty in interpreting the child's mental states. Nor were there any significant associations found for Executive functions, and Processing speed. Depressive and anxiety symptoms were found to correlate negatively with the PRFQ-fi subscale Appropriateness of reasoning about mental states underlying child's reactions, but positively with the PRFQ-fi subscale Understanding the opaque nature of mental states. The results that both verbal learning and verbal intelligence are linked with aspects of maternal mentalization has a potential to be utilized in approaches to early intervention, especially among the at-risk mothers needing support in connecting with their child. E.g., via modeling, rather than merely verbalizing, the child’s mental states for the mother during visits at the child health clinic. Further research might explore the finding that higher depressive and anxiety symptoms are not inevitably harmful for maternal mentalization and these associations may be more complex than thought. However, the information that higher symptoms are not inevitably harmful for maternal mentalization could be of importance for a new mother worrying about her depressive/anxiety symptoms, thus potentially supporting the quality of mother-child relationship.
Keywords: maternal mentalization, cognitive functions, PRFQ, CogState, depressive symptoms, anxiety symptoms